Pengembangan Model Adaptasi Psikososial terhadap Kualitas Hidup Pasien Hemodialisis - Sari, Ni Made Sekar; Widyawati, Ika Yuni; Ulfiana, Elida; Abdulloh, Ahmad Abdul Ghofar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Based on Calista Roy's adaptation theory and self-determination theory, this study aims to develop a psychosocial adaptation model for hemodialysis patients, affecting their quality of life. The method used was a non-probability sampling technique through purposive sampling, with a sample size of 119 hemodialysis patients at the Bina Husada Cipta Canthi Clinic (BHCC) and the Semesta Mandiri Clinic (KSM), calculated using the rule of thumb. Statistical analysis used SEM-PLS. The results showed that stimulus factors, interdependence, self-concept-resilience, and role function influenced quality of life. At the same time, basic psychological needs did not affect the quality of life of hemodialysis patients. This study concludes that the psychosocial adaptation model for hemodialysis patients' quality of life is valuable. Therefore, dialysis unit staff are expected to use this psychosocial adaptation development guideline to improve the quality of comprehensive hemodialysis unit services for hemodialysis patients. Keywords: Adaptation, Hemodialysis, Quality of Life, Psychological, Social